Genomic analysis of circulating HIV and hepatitis C virus infections and coinfections in Cameroon: 2005–2006 and 2015–2016 - Tamim, Sana; Nwobegahay, Julius; Fepa Kwesseu, Armelle Gaelle; Guiateu Tamo, Ida Marlene; Djuidje Ngounoue, Marceline (Frontiers in Tropical Diseases, 2023)
Introduction In humans, RNA viruses are responsible for a wide range of acute, chronic, emerging and re-emerging infections. Human Immunodeficiency virus (HIV) and hepatitis C virus (HCV) rank as some of the most important public health challenges affecting Africa. Methods We performed enzyme-linked immune-sorbent assays to confirm positive specimens, and the genomic characterization on two cohorts of people living with HIV in Douala and Yaoundé for the periods 2005-2006 and 2015-2016. These groups were tested for co-infection with HCV using the enzyme-linked immunosorbent assays. Viral RNA was extracted from positive patients’ plasma samples by QIAGEN method, and specific primers were used to amplify the genes of interest on HIV and HCV genomes. The amplification products were subsequently cloned and sequenced. The nucleotide sequences were aligned, genotyped and phylogenetically analyzed. Results The HIV isolate identified in this study belongs to HIV-1 group M Subtype A1. The HCV subtypes characterized in this study are 1h and 4t corresponding to the dominant strains that circulate in Cameroon. Phylogenetic analysis of the HCV NS5B gene showed that the study viruses cluster with Gabonese, Canadian, and previously sequenced viruses from Cameroon. Conclusion and perspectives These results shed light on the genetic diversity of HIV and HCV in Cameroon. Virulent HCV infections are common in Cameroon, and therefore there is a great need for further analysis of the viral evolutionary and spatio-temporal patterns.